Bird diversity in 'paricá' (Schizolobium amazonicum Huber ex Ducke) plantations and forest fragments in Eastern Amazon: taxonomic diversity, ecological guilds, and functional trait composition. (2nd January 2023) - Barros, Fernanda de Carvalho; Almeida, Sara Miranda; Cerqueira, Pablo Vieira; Silva, Larissa Cardoso; Santos, Marcos Pérsio Dantas
ABSTRACT: Monoculture may drastically reduce biodiversity and change communities' structure due to habitat simplification. Plantations of Schizolobium amazonicum Huber ex Ducke ('paricá') has been expanding in the Amazon region due to the increased demand for veneer and plywood production. Our objective was to assess whether bird communities in paricá plantations and forested areas differ in terms of composition, richness, abundance, trophic structure, and functional trait composition. This study was conducted in young paricá plantations (1 to 5 years) and forest fragments in eastern Amazon, state of Pará, Brazil. We sampled birds in five plantation sites (each paired with a nearby forested area) using both the point-count method and mist nets. We recorded 208 bird species, 132 in forest fragments and 94 in plantations. Comparatively, habitats showed distinct species composition and trait composition, with few shared species (n = 18). Paricá plantations did not support forest species, while forest fragments harbored specialized bird communities that are more sensitive to environmental change as well as endangered species. In this way, the protection of these forested areas surrounding paricá plantations is a priority for forest biodiversity conservation, given the rapid deforestation in the Brazilian Amazon.